Pengaruh Pengetahuan, Sikap, Fasilitas, Pengelola Pasar, Terhadap Perilaku Flu Burung pada Pedagang dan Pemotong Unggas - Putu Yuni Fitria Dewi; Purwanta Purwanta; Sri Mulyani (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2017)
Background: There were 131 cases of bird deaths in Yogyakarta on 12-16 May 2014 due to H5N1 virus. Live poultry market as one of the crucial points in the transmission of avian influenza should be handled seriously. Therefore, it is necessary to know the behaviors of poultry traders and slaughterers working in the market, as those are at high risk of contracting avian influenza.Objective: This research aimed to determine the correlation among knowledge, attitudes, facilities, and market administrators toward behaviors of poultry traders and slaughterers in preventing avian influenza in Terban Market, Yogyakarta.Methods: This was a quantitative research with cross-sectional design. Data were obtained via questionnaires and observations of 100 people consisted of poultry traders and slaughterers in Terban Market chosen by proportionate stratified random sampling technique in September 2014. Data were then analyzed using Somers’D for the bivariate analysis and logistic regression for the multivariate analysis.Results: The results showed that the respondents’ knowledge was high (65%) while attitudes (66%), facilities (53%), behaviors of market administrators (44%), and behaviors of poultry traders and slaughterers (55%) were satisfactory. There were correlation among knowledge (p=0,015), attitudes (p=0,000), facilities (p=0,010), and behaviors of market administrators (p=0,001) toward poultry traders and slaughterers behaviors. Attitudes was the most dominant factor influencing live poultry traders and slaughterers behaviors (OR=7,296). Conclusion: Knowledge, attitudes, facilities, and behaviors of market administrators influenced poultry traders and slaughterers behaviors in preventing avian influenza in Terban Market, Yogyakarta.ABSTRAKPendahuluan: Pada tanggal 12-16 Mei 2014, di Yogyakarta terjadi 131 kasus kematian unggas akibat virus H5N1. Pasar unggas hidup yang merupakan salah satu titik kritis dalam penularan flu burung, harus mendapatkan penanganan yang serius. Untuk itu perlu diketahui perilaku pedagang dan pemotong unggas yang bekerja di pasar sebagai pihak yang beresiko tinggi tertular flu burung.Tujuan: Tujuan penelitian untuk mengetahui pengaruh pengetahuan, sikap, fasilitas, dan pengeiola pasar terhadap perilaku pencegahan flu burung pada pedagang dan pemotong unggas di Pasar Terban Yogyakarta.Metode: Penelitian berjenis kuantitatif dengan rancangan cross sectional. Pengambilan data menggunakan kuesioner dan observasi pada 100 orang pedagang dan pemotong unggas di Pasar Terban, dengan teknik proportionate stratified random sampling pada bulan September 2014. Analisis bivariat menggunakan Somers’D, analisis multivariat menggunakan regresi logistik.Hasil: Berdasarkan hasil penelitian, pengetahuan responden tinggi (65%), sedangkan sikap (66%), fasilitas (53%), perilaku pengelola pasar (44%), dan perilaku pedagang dan pemotong unggas (55%) cukup baik. Terdapat pengaruh antara pengetahuan (p=0,015), sikap (p=0,000), fasilitas (p=0,010), pengelola pasar (p=0,001) dengan perilaku pedagang dan pemotong unggas. Sikap adalah faktor yang paling dominan mempengaruhi perilaku pedagang dan pemotong unggas (OR=7,296).Kesimpulan: pengetahuan, sikap, fasilitas, dan perilaku pengelola pasar mempengaruhi perilaku pencegahan flu burung pada pedagang dan pemotong unggas di Pasar Terban, Yogyakarta.